New cholinesterase inhibitory constituents from Lonicera quinquelocularis - Khan, D. (Public Library of Science, 2014)
A phytochemical investigation on the ethyl acetate soluble fraction of Lonicera quinquelocularis (whole plant) led to the first time isolation of one new phthalate; bis(7-acetoxy-2-ethyl-5-methylheptyl) phthalate (3) and two new benzoates; neopentyl-4- ethoxy-3, 5-bis (3-methyl-2-butenyl benzoate (4) and neopentyl-4-hydroxy-3, 5-bis (3-methyl-2-butenyl benzoate (5) along with two known compounds bis (2-ethylhexyl phthalate (1) and dioctyl phthalate (2). Their structures were established on the basis of spectroscopic analysis and by comparison with available data in the literature. All the compounds (1-5) were tested for their acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory activities in dose dependent manner. The IC50 (50 inhibitory effect) values of compounds 3 and 5 against AChE were 1.65 and 3.43 Î¼M while the values obtained against BChE were 5.98 and 9.84 Î¼M respectively. Compounds 2 and 4 showed weak inhibition profile. Â© 2014 Khan et al.